Olexandr Ivanovych Bodnia - "ORTHOPAEDICS, TRAUMATOLOGY AND PROSTHETICS", Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is devoted to Alexander Ivanovich, Doctor of Medical Sciences, Professor of the Department of Traumatology and Orthopedics, Odessa National Medical University.